Prevalence of high blood pressure among adolescents and association with anthropometric indicators Prevalência de pressão arterial elevada em adolescentes e associação com indicadores antropométricos - De Araujo Pinto A.* (2017)
Introduction: Physical inactivity, sedentary behavior and poor nutrition are behaviors currently adopted by adolescents, which have facilitated the development of cardiovascular diseases such as high blood pressure. Study design: This is a school-based epidemiological study with a cross-sectional design. Objective: A analyze the high blood pressure (HBP) prevalence and its association with anthropometric indicators. Methods: Participants were 202 adolescents from Sao José-SC. Measures of body weight, height and waist circumference (WC) were used to calculate the anthropometric indicators of Body Mass Index (BMI), Conicity Index (C index) and Waist-to-Height Ratio (WHR). Blood pressure was measured by a digital Omrom HEM 742. Results: The prevalence of HBP among the adolescents was 10.9%. Overweight adolescents (OR= 5.68; 95%CI= 1.99-16.24) and those with high WC (OR= 7.67; 95%CI= 2.54-23.19) and high WHR (OR= 5.88; 95%CI= 1.71-20.25) were more likely to present HBP than their normal weight and with healthy WC and WHR peers. Conclusion: The results of the present study demonstrated that one in ten adolescents presented HBP. Body Mass Index (overweight), WC and WHR (unhealthy conditions) were associated to the outcome.